Making Sense of the Linkage among Iranian English Language Teachers’ Grit Level, Self-Efficacy, and their Continuing Professional Development - Faravani, Akram (Asian Journal of Contemporary Education, 2022)
This study discusses the professional issues concerning Iranian EFL teachers’ grit level, self-efficacy, and continuing professional development. Teacher Continuing Professional Development is an essential factor in enhancing teaching practice from Initial Teacher Education right through to headship. However, there has been less previous evidence for the relationships between teachers’ self-efficacy and Grit level with their continuing professional development (CPD). The researcher proposed a new model of interrelationships among Iranian EFL teachers using AMOS software to illuminate this uncharted area. 204 EFL teachers (111 males and 93 females) teaching in different private language institutes in Mashhad, Iran, were the population selected through convenience sampling. The research instruments used include Short Grit Scale, Teachers’ Self-Efficacy Scale, and teachers’ Continuing Professional Development questionnaire. The results of structural equational modeling revealed that teachers’ grit and self-efficacy are significant positive predictors of CPD. Moreover, the study results revealed that teacher grit was predicted only by self-efficacy. Pearson correlation analysis showed the highest correlation between self-efficacy and CPD and the lowest correlation between grit and CPD. Along the line, various pedagogical implications arose from the research results for teachers, administrators, and the ministry of education.